PENERAPAN ALGORITMA DEEP LEARNING UNTUK PENGEMBANGAN CHATBOT YANG DIGUNAKAN UNTUK KONSULTASI DAN PENGENALAN TENTANG VIRUS COVID-19 - Nur Rohim; Eri Zuliarso (STEKOM PRESS, 2022)
Covid-19 pandemic that hit almost all countries and no exception beloved our country Indonesia, has resulted in destruction and the collapse of the community’s economy. At the same time there is information about the covid-19 virus that still needs to be questioned about the validity of the source. With the development of technology in today’s era, it is easier for us to filter information that has valid sources so that there are no misunderstandings about the information obtained. So on this basis, this study aims to develop a chatbot model regarding Covid-19 in a relevant and fast manner according to the questions and statements entered. Chatbot itself is an Artificial Intelligence-based program or we can call it a digital assistant, which can simulate user conversations or chats like humans through an application either based on Android or the web. By using chatbot technology, users can get valid and relevant answers whose sources are clear so as not to cause anxiety and also make it easier for users to get information about the Covid-19 virus. Keywords: Covid-19; Technology; Chatbot; Artifical Intelligence